# cot θ tan (

Consider L.H.S.

= cot θ tan (90° -θ) - sec (90° - θ)cosec θ +√3tan 12°tan 60°tan 78°

= cot θ cot θ - cosec θ cosec θ +√3 tan 60° tan 12° tan 78°

= cot2 θ – cosec2 θ +√3 tan 60° tan 12° tan(90-12)°

= - (cosec2 θ - cot2 θ) +√3 tan 60° tan 12° cot 12°

= - 1 + √3(√3 × tan 12° cot 12°)

= - 1 + √3(√3 × 1)

= - 1 + 3

= 2 = R.H.S.

Hence, proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric Identities55 mins
Trigonometric Ratios of Specified Angles38 mins
Trigonometric Ratios46 mins
Heights and Distances - II45 mins
Heights and Distances - I54 mins
Introduction of Geometric Progression60 mins
Introduction of Metal and Non Metal59 mins
How to Revise Chemistry45 mins
Nelson Mandela : Long Walk to Freedom42 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Choose the correcRS Aggarwal - Mathematics

If A, B and C areRS Aggarwal - Mathematics